Brannigan's Land - Book 1 - Johnstone, William W.; Johnstone, J. A. (Thorndike, Maine : Center Point Large Print, 2022)
"Once a respected lawman in Kansas and Oklahoma, Ty Brannigan ended his career as town marshal of Warknife while he was still young enough to marry, start a family, and raise cattle. Now nearly sixty, hes a proud husband, father of four, and proprietor of the Powderhorn Ranch on the outskirts of his old stomping grounds. Its been close to twenty years since Brannigan hung up his six-guns. Now hes more content wrangling cows than criminals . . . But for every remorseless outlaw Brannigan put in jail, noosed, or left the vultures, he made even more enemies. Thieves and killers looking to settle old scores have tracked the ex-lawdog to his ranch. Theyve made the mistake of targeting his wife and children--only to discover that Ty Brannigan enforces his own law with a lightning-fast draw and a deadshot aim."--
Keywords: Ranchers -- Fiction; Gunfighters -- Fiction; Frontier and pioneer life -- West (U.S.); Fiction; Wyoming -- Fiction; Fiction; Western fiction